Hunting for eclipses: high-speed observations of cataclysmic variables. Issue 4 (23rd November 2016) - Hardy, L. K.; McAllister, M. J.; Dhillon, V. S.; Littlefair, S. P.; Bours, M. C. P.; Breedt, E.; Butterley, T.; Chakpor, A.; Irawati, P.; Kerry, P.; Marsh, T. R.; Parsons, S. G.; et al.
Abstract: We present new time-resolved photometry of 74 cataclysmic variables (CVs), 47 of which are eclipsing. Thirteen of these eclipsing systems are newly discovered. For all 47 eclipsing systems, we show high cadence (1–20 s) light curves obtained with the high-speed cameras ULTRACAM and ULTRASPEC. We provide new or refined ephemerides, and supply mid-eclipse times for all observed eclipses. We assess the potential for light-curve modelling of all 47 eclipsing systems to determine their system parameters, finding 20 systems that appear to be suitable for future study. Systems of particular interest include V713 Cep, in which we observed a temporary switching-off of accretion; and ASASSN-14mv and CSS111019:233313−155744, which both have orbital periods well below the CV period minimum. The short orbital periods and light-curve shapes suggest that they may be double degenerate (AM CVn) systems or CVs with evolved donor stars.